The Effect Of Reynolds Number At Fluid Flow In Porous Media - L. Buchori; M. D. Supardan; Y. Bindar; D. Sasongko; IGBN Makertihartha (Reaktor, 2002)
In packed bed catalytic reactor, the fluid flow phenomena are very complicated because of the fluid and solid particles interaction to dissipate the energy. The governing equations need to be developed to the forms of specific models. Flows modeling of fluid flow in porous media with thw absence of the convection and viscous terms have been considerably developed such as Darcy, Brinkman, Forchheimer, Ergun, Liu, et.al and Liu and Masliyah models. These equations usually are called shear factor model. Shear factor is determined by the flow regime, porous media characteristics and fluid properties. It is true that these models are limited to condition whether the models can be applied. Analytical solution for the model types above is available only for simple one-dimentionalcases. For two or three-dimentional problem, numerical solution is the only solution. The present work is aimed to developed a two-dimentional numerical modeling flow in porous media by including the convective and viscous term. The momentum lost due  to flow and porous material interaction is modeled using the available Brinkman-Forchheimer and Liu and Masliyah equations. Numerical method to be used is finite volume method. This method is suitable for the characteristic of fluid flow in porous media which is averaged by a volume base. The effect of the solid and fluid interaction  in porous media is the basic principle of the flow model in porous media. The momentum and continuity  equations are solved for two-dimentional cylindrical coordinate. The result were validated with the experimental data . the result show a good agreement in their trend between Brinkman-Forchheimer equqtion with the Stephenson and Stewart (1986) and Liu and Masliyah equation with Kufner and Hoffman (1990) experimental data.Keywords : finite volume method, porous media, Reynold number, shear factor